Consumer preferences for chlorine washed chicken, attitudes to Brexit and trade agreements - Kelvin G. Balcombe; Dylan Bradley; Iain M. Fraser (University of Kent, School of Economics, 2021)
This research employs two alternatively framed but formally equivalent discrete choice ex- periments that examine UK consumer preferences regarding chlorine washed chicken. One is framed in a common purchase format, the other employs a format that endows respondents with a voucher that they can use to redeem for a chicken product, or exchange, in part, for an alternative chicken product or cash. We find that the difference in our value estimates is small regardless of how we implement our choice experiment. Our analysis also differentiates the value estimates by respondent attitude to Brexit. The results reveal that being positively disposed toward Brexit means that respondents are less likely to value chlorine washed chicken negatively. Yet, of equal or greater significance, those respondents who hold positive attitudes with regard to Brexit still value EU food safety standards and quality assurance schemes such as Red Tractor highly. This suggests that attitudes to Brexit and preferences regarding food do not necessarily align in support of trade agreements that may require the UK to lower ex- isting food safety and animal welfare standards. Potential policy solutions to ensure consumer preferences are satisfied are discussed.
Keywords: Q18; Q17; I18; 330; Chlorinated Chicken; Willingness to Pay; Discrete Choice Experiment; Brexit; Trade Policy; Red Tractor